2016
DOI: 10.1002/elsc.201500083
|View full text |Cite
|
Sign up to set email alerts
|

The influence of methyl jasmonate, cholesterol and l‐arginine on solasodine production in hairy root culture of Solanum mammosum

Abstract: The increasing demand of diosgenin for high-revenue synthesis of steroid hormones by the pharmaceutical industries has driven researchers to look for other alternatives. Solasodine which was reported to be present in Solanum mammosum is known to be a potential source. The present study highlighted that added methyl jasmonate, cholesterol and l-arginine into the modified liquid full-strength Murashige and Skoog (MS) medium (with ammonium to nitrate ratio 10.3 mM: 39.4 mM, and 4% (w/v) sucrose) could influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The application of optimum concentration of MJ (300 µM) along with the precursors such as cholesterol (100 mM) and L‐arginine (1000 µM) supplemented modified liquid MS medium on 20‐days‐old HRCs (hairy root line‐ATCC31798 and line‐A4) of Solanum mammosum improved solasodine productivity five‐fold (4.5 mg g −1 ) with a high‐biomass accumulation (in average 190 mg DW) compared to control HRCs cultured without both the elicitor and precursor treatment .…”
Section: Elicitors and Their Effects On Hrcsmentioning
confidence: 99%
“…The application of optimum concentration of MJ (300 µM) along with the precursors such as cholesterol (100 mM) and L‐arginine (1000 µM) supplemented modified liquid MS medium on 20‐days‐old HRCs (hairy root line‐ATCC31798 and line‐A4) of Solanum mammosum improved solasodine productivity five‐fold (4.5 mg g −1 ) with a high‐biomass accumulation (in average 190 mg DW) compared to control HRCs cultured without both the elicitor and precursor treatment .…”
Section: Elicitors and Their Effects On Hrcsmentioning
confidence: 99%
“…Organ cultures, including shoot cultures, are often used in studies on feeding experiments e.g. [9,10,14,15,[27][28][29]. L-phenylalanine is one of frequently used precursors in feeding experiments [10].…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the production levels can be further improved by the application of elicitors in the hairy root culture systems. Several studies have shown that enhanced production of different classes of metabolites can be achieved in hairy root cultures of solanaceous plants of Anisodus acutangulus , Atropa acuminata , A. baetica , A. belladonna , Brugmansia candida , Datura metel , D. stramonium , Hyoscyamus albus , H. muticus , H. reticulatus , Solanum mammosum , S. myriacanthum , S. trilobatum , and Withania somnifera , upon elicitation ( Mehmetoğlu and Curtis, 1997 ; Kuroyanagi et al., 1998 ; Pitta-Alvarez and Giulietti, 1998 ; Jacob and Malpathak, 2005a ; Jacob and Malpathak, 2005b ; El Jaber-Vazdekis et al., 2008 ; Doma et al., 2012 ; Kai et al., 2012a ; Shilpha et al., 2015 ; Ooi et al., 2016 ; Srivastava et al., 2016 ; Moharrami et al., 2017 ; Shakeran et al., 2017 ; Amdoun et al., 2018 ; Moradi et al., 2020 ; Fattahi et al., 2021 ) ( Supplementary Table 1 ).…”
Section: Strategies Adopted For Enhancement Of Secondary Metabolite P...mentioning
confidence: 99%